Meteorological characteristics of Antarctic inland station, Dome Fuji (scientific paper) - Yamanouchi, Takashi; Hirasawa, Naohiko; Hayashi, Masahiko; Takahashi, Shuhei; Kaneto, Susumu (2003)
P(論文) Surface meteorological observations were carried out during 1995 and 1997, and extended atmospheric science observations were carried out in 1997 as a sub program of "Atmospheric Circulation and Material Cycle in the Antarctic (1997-2001)" at Dome Fuji Station (77°19'S, 39°42'E) where deep ice core drilling was done. The annual mean surface air temperature was -54.4°C with the lowest record of -79.7°C. The mean wind speed was 5.8 m/s with no clear prevailing wind direction. From aerological soundings, temperature profiles are described; they are characterized by a strong surface inversion such as 25°C, on a normal winter day. Abrupt warming occurred several times a year; the largest showed 40 degree temperature increase within two days between 17 and 19 July 1997. The event was associated with the intrusion of an anticyclone, "a blocking high", and many drastic phenomena such as large accumulation of snow followed this event. departmental bulletin paper